Assessing the impact of international trade on human development outcomes in Nigeria - Iyabo A. Olanrele; Sebil Olalekan Oshota (Future Business Journal)
Abstract This study examines the impact of trade per capita on human development outcomes in Nigeria over the period 1990–2022. Using data from the United Nations Development Programme (UNDP), World Development Indicators (WDI), and other national source, the study employs Autoregressive Distributed Lag (ARDL) for the main analysis and the Dynamic Ordinary Least Square (DOLS), Fully Modified Ordinary Least Squares (FMOLS) and Canonical Cointegration Regression (CCR) for robustness checks. The results reveal that trade per capita significantly enhances human development, particularly by improving gross national income per capita and life expectancy, while its effects on education outcomes are less consistent. Furthermore, GDP per capita growth is found to negatively affect life expectancy in certain cases, suggesting that economic growth alone does not guarantee human development unless accompanied by equitable resource distribution. Public health expenditure positively influences both life expectancy and education, emphasizing the importance of targeted investments. These findings underscore the need for policies that enhance trade openness while simultaneously addressing infrastructural gaps and investing in health and education sectors to ensure sustainable and inclusive development.